The Influence of Human Relation and Work Environment on Employee Performance at Industry and Trade Office of North Sumatera Province - Nurul Fadhilah; Prihatin Lumbanraja; Meilita Tryana Sembiring (Quantitative Economics and Management Studies, 2023)
The study aims at analyzing the influence of human relation and work environment on employee performance at the office of Industry and Trade in North Sumatera. The respondents of this study consists of 71 employees of the Industry and Trade office. In collecting data, the study administered the questionnaires which were then analyzed using multiple linear regression analysis. The equation model was managed through statistical procedures using the SPSS for Windows version 21 application.The results of the research showed that human relation and work environment partially have a positive and significant effect on the performance of employees at the office of Industry and Trade of North Sumatra Province. In addition, human relation and work environment simultaneously have a positive and significant effect on the performance of employees of the office of Industry and Trade of North Sumatra Province.